Differences in cognitive life skills, knowledge, and attitudes between primary school students - Indraswari, Ratih; Widjanarko, Bagoes; Kusumawati, Aditya; Handayani, Novia (Intelektual Pustaka Media Utama, 2024)
Adolescents who can think critically and make the right decisions reported delaying the practice of sexual pre-marital. This study describes the cognitive life skills, knowledge, and attitudes in the reproductive health context among primary school students. This research is a cross-sectional study conducted on 12.689 grade 4-6 primary school students in Semarang, Central Java, Indonesia. The Mann-Whitney U-test investigates the differences between male and female students’ decision-making skills, critical thinking skills, knowledge, and attitude. Most children (62.1%) stated that deciding something was difficult. Only 36.8% of children get ideas from other people when having a task to do. There are differences in knowledge (p-value=0.000) and attitudes (p-value=0.000) about reproductive health, as well as critical thinking skills (p-value=0.002) between males and females. There is no significant difference between males and females in terms of decision-making skills (p-value=0.202). There are differences in knowledge and attitudes about reproductive health and critical thinking skills between male and female students. However, there is no significant difference between males and females regarding decisionmaking skills. The Ministry of Health should design a life skills education method for pre-pubertal children considering sex segregation.